2021
DOI: 10.1136/bcr-2021-243979
|View full text |Cite
|
Sign up to set email alerts
|

Non-tuberculous mycobacteria infection treated with intermittently inhaled high-dose nitric oxide

Abstract: Mycobacterium abscessus is an emerging multidrug-resistant non-tuberculous mycobacterium (NTM) with high prevalence in patients with cystic fibrosis. However, studies on antimicrobial susceptibilities and effective treatments against M. abscessus are still limited. Nitric oxide (NO) is important in innate immune response to various infections, including mycobacterial infections. In this case study, we describe a compassionate treatment of inhaled NO (iNO) at 150–250 ppm for 4 weeks. The dosing strategy propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The use of inhaled NO by Yaacoby-Bianu et al in 2018 in two cystic fibrosis patients with pulmonary MAB resulted in a reduction in bacterial load as measured by quantitative polymerase chain [ 78 ]. The use of inhaled NO by Goldbart et al in a CF patient with pulmonary MAB showed bacterial growth inhibition as well as improvement of lung pathology on CT [ 79 ]. The observations from these case reports show that NO is safe and well tolerated and could play a crucial role in the treatment of NTM pulmonary disease [ 71 , 78 , 79 ].…”
Section: Methodsmentioning
confidence: 99%
“…The use of inhaled NO by Yaacoby-Bianu et al in 2018 in two cystic fibrosis patients with pulmonary MAB resulted in a reduction in bacterial load as measured by quantitative polymerase chain [ 78 ]. The use of inhaled NO by Goldbart et al in a CF patient with pulmonary MAB showed bacterial growth inhibition as well as improvement of lung pathology on CT [ 79 ]. The observations from these case reports show that NO is safe and well tolerated and could play a crucial role in the treatment of NTM pulmonary disease [ 71 , 78 , 79 ].…”
Section: Methodsmentioning
confidence: 99%
“…The authors also hypothesized that prolonged intermittent iNO treatment beyond 3 weeks could increase the susceptibility of NTM biofilm to antibiotics and achieve improved bactericidal activity in CF airways [ 71 ]. However, more recent case reports showed that even longer durations (up to 29 days) and higher doses of iNO (up to 250 ppm) failed to induce the eradication of infective microorganisms [ 72 , 73 ].…”
Section: High-dose Exogenous No As An Antimicrobial Treatmentmentioning
confidence: 99%
“…With several clinical trials under way (NCT02498535; refs. [ 119 , 120 ]), success in the application of NO as an antibiofilm agent might be based on a combination of antimicrobial, antibiofilm, and host physiological effects [ 121 ]. The antimicrobial peptide LL-37 has been shown to possess a potent antibiofilm, rather than antimicrobial activity against various pathogens, such as P. aeruginosa and Escherichia coli ( Table 2 ; refs.…”
Section: Innovative Strategies To Overcome Antimicrobial Tolerance In...mentioning
confidence: 99%